2014
DOI: 10.1016/j.imavis.2014.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Using a Discrete Hidden Markov Model Kernel for lip-based biometric identification

Abstract: Abstract-In this paper, a novel and effective lip-based biometric identification approach with the Discrete Hidden Markov Model Kernel (DHMMK) is developed. Lips are described by shape features (both geometrical and sequential) on two different grid layouts: rectangular and polar. These features are then specifically modeled by a DHMMK, and learnt by a support vector machine classifier. Our experiments are carried out in a ten-fold cross validation fashion on three different datasets, GPDS-ULPGC Face dataset, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…In 2014, Travieso et al. [21] developed a lip biometric approach based on shape information using a Discrete Hidden Markov Model (DHMMK). The lips are described by shape features (geometrical and sequential), which are then modelled by a DHMMK and classified using an SVM.…”
Section: Literature Studymentioning
confidence: 99%
“…In 2014, Travieso et al. [21] developed a lip biometric approach based on shape information using a Discrete Hidden Markov Model (DHMMK). The lips are described by shape features (geometrical and sequential), which are then modelled by a DHMMK and classified using an SVM.…”
Section: Literature Studymentioning
confidence: 99%
“…In the analysis of mammographic images with noise, a method was proposed for estimating the fractal dimension in 3D, modelling it as a fractional brownian motion and using the Spectral Power Density of Fourier and its correlation with the roughness. It has been found that an increase in the noise of the image increases its fractal dimension [36,37]. In our study, we will use the counting method of boxes (box-counting), taking into account some of the recommendations of the method to avoid excessive variations:…”
Section: Calculation Of the Fractal Dimensionmentioning
confidence: 99%
“…In general, features can be classified into texture, shape, and color. The form and position of the lip furrows were analyzed in texture features such as Markov models [16], radon transform [17], Bifurcation's analysis [18], HT [19], Top_Hat [20], gabor filter, local binary pattern (LBP) [21], dynamic time warping (DTW) [22], [23], statical analysis [24], [25], scale invariant feature transform (SIFT), speeded up robust features (SURF) [26], location and inclination of the furrows [27], LBP, area and perimeter [28] and principal component analysis (PCA) [29]. Shape features include general geometric properties of the lips [30], Rotation, scale, and translation invariant image [31], and Shape descriptors [32].…”
Section: Introductionmentioning
confidence: 99%